Development and initial performance of a miniature axial flow blood pump using magnetic fluid shaft seal - Okamoto, Eiji; Yano, Tetsuya; Sekine, Kazumitsu; Inoue, Yusuke; Shiraishi, Yasuyuki; Yambe, Tomoyuki; Mitamura, Yoshinori (Journal of artificial organs, 2023)
In this study, we developed a new catheter-mounted micro-axial flow blood pump (MFBP) using a new miniature magnetic fluid shaft seal (MFSS). The prototype of the catheter-mounted MFBP had a maximum diameter of 8 mm and a length of 50 mm. The new MFSS composed a neodymium magnet ring, an iron ring, and a magnetic fluid particularly designed for the MFSS. The new MFSS had outer and inner diameters of 4.0 mm and 2.6 mm, respectively, and a length of 3.0 mm. The sealing pressure of the MFSS was calculated to be 432 mmHg using FEM (Finite Element Method) result; therefore, the MFSS had sufficient sealing pressure for the catheter-mounted MFBP. The friction loss of the MFSS included the friction owing to the viscosity of the magnetic fluid and the magnetic force between the iron ring and ring magnet. The total friction loss of the MFSS was 0.08–0.09 W in the pump operational speed range from 22,000 to 35,000 rpm. From the in vitro experimental results, the catheter-mounted MFBP using the MFSS had a pump output of 3 L/min. against a differential pressure of 60 mmHg, and the pump characteristics of the MFBP were almost the same as those of Impella 5.0.